ANALISIS KEKERASAN YANG DIALAMI IQBAL RAMADHAN DITINJIAU DARI PERSPEKTIF PANCASILA SILA KEDUA - Nora Divina Ramadani Ramadani (Civic Edu : Jurnal Pendidikan Kewarganegaraan, 2024)
This research analyzes the violence experienced by Iqbal Ramadhan, an assistant lawyer, during a demonstration against the Revision of the Regional Election Law in Jakarta. The repressive actions by security forces against Iqbal, which included physical and psychological violence, showed a deviation from the principle of "Just and Civilized Humanity" in the second principle of Pancasila. In this research, the author examines the arrest process, the forms of violence experienced, as well as the physical and psychological impacts experienced by Iqbal. This case reflects the tension between the right to express an opinion and the authorities' efforts to maintain public order. This research highlights the importance of respecting human rights and peaceful and civilized conflict resolution, as mandated in Pancasila. The violence experienced by Iqbal Ramadhan not only violated human rights, but also violated the values ​​of humanity and justice contained in Pancasila. This incident demands an evaluation of the way the authorities handle demonstrations so that they are more based on human values ​​and justice.